AKTIVITAS ANTIOKSIDAN CENDAWAN SUKU PLEUROTACEAE DAN POLYPORACEAE DARI HUTAN UI - Abdul Mun’im; Azizahwati Azizahwati; Trastiana Trastiana (Jurnal Ilmiah Farmasi, 2008)
ABSTRACTSix mushrooms, Lentinus sajor-caju, Lentinus sp, Panellus sp. Polyporusgrammocephalus, Polyporus cf floccipes and Pseudopiptoporus sp (Pleurotaceae andPolyporaceae Family) were used to study antioxidant properties. Ethanolic extract of themushrooms showed scavengging ability on 1,1-diphenyl-2-picrylhydrazil (DPPH) radical. In thethyociante method, there is no significant inhibition of lipid peroxidation activities between samplesand positive controls. Phytochemical identification on ethanolic extract of Pseudopiptoporus spshowed that terpenes were the major component. This finding suggested that terpenes areresposible for antioxidant activity.Keywords: Antioxidant activity, DPPH, Pleurotaceae, Polycarpaceae, Thiocyanate method